2020
DOI: 10.1016/j.jmoldx.2020.07.005
|View full text |Cite
|
Sign up to set email alerts
|

The Comprehensive Comparison of Bacterial Artificial Chromosomes (BACs)–on-Beads Assay and Copy Number Variation Sequencing in Prenatal Diagnosis of Southern Chinese Women

Abstract: Bacterial artificial chromosomes (BACs)eon-Beads (BoBs) assay and copy number variation sequencing (CNV-seq) are two frequently used methods in today's prenatal diagnosis. Several studies were conducted to investigate the performance of each approach, but they were never compared side by side. In this article, a comprehensive comparison of BoBs and CNV-seq was conducted using 1876 amniotic fluid and umbilical cord blood samples collected from Fujian Maternity and Child Health Hospital between 2015 and 2019. Ka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 21 publications
1
7
3
Order By: Relevance
“…Consistent with other studies (Tao et al, 2019;Xu et al, 2020), we found that PNBoBs ™ , at least for common aneuploidies, was highly concordant with karyotyping. Some have recommended that a positive RAD result, without karyotyping, can be directly used as a basis for medical decision-making in clinical management (Ogilvie et al, 2005;Comas et al, 2010).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Consistent with other studies (Tao et al, 2019;Xu et al, 2020), we found that PNBoBs ™ , at least for common aneuploidies, was highly concordant with karyotyping. Some have recommended that a positive RAD result, without karyotyping, can be directly used as a basis for medical decision-making in clinical management (Ogilvie et al, 2005;Comas et al, 2010).…”
Section: Discussionsupporting
confidence: 92%
“…With the clinical application of PNBoBs, different perspectives have emerged; some have suggested that it can replace traditional karyotyping (Piotrowski et al, 2012), arguing that PNBoBs ™ can detect most clinical cases of pCNV and that it possesses advantages over traditional karyotyping. However, a more recent, alternative view is that PNBoBs ™ should be replaced by genome-wide CNV analytical techniques, such as CNV-seq (Xu et al, 2020), regardless of the indication for prenatal diagnosis. These different views reflect the complexity of and lack of consensus on application criteria for PNBoBs ™ in prenatal diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations